2011
DOI: 10.1063/1.3590744
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sol-age on the surface and optical properties of sol-gel derived mesoporous zirconia thin films

Abstract: Effects of aging time and annealing temperature on structural and optical properties of sol-gel ZnO thin films AIP Advances 7, 065213 (2017) Effect of annealing temperature on optical and electrical properties of based nanocomposite thin films

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…For E g calculation, there are many models based on Tauc's plot. 29,30 We used the method as given by Chen et al 29 and found that E g remains as 3.4 eV for all films prepared at different power densities.…”
mentioning
confidence: 99%
“…For E g calculation, there are many models based on Tauc's plot. 29,30 We used the method as given by Chen et al 29 and found that E g remains as 3.4 eV for all films prepared at different power densities.…”
mentioning
confidence: 99%
“…There is a lack of the theoretical support for applying the Tauc plot to nanocrystals, and the size dependence of the exponent n may be caused by quantum confinement, that may result in elevated bandgap values . As for porosity, the Tauc method was successfully applied to calculate bandgap in mesoporous zirconia thin films …”
Section: Resultsmentioning
confidence: 99%
“…These films were prepared with a sol-gel dip coating technique using the 3-day aged sol. Details of ZrO 2 film preparation and effect of ageing of sol on deciding the pore size and porosity are elaborated in our earlier studies [22,23]. These films were dipped in aqueous solution of citrate capped Ag nanoparticles (Ag concentration 0.1 M) and Ag-NO 3 /tri-sodium citrate (TSC) molecular ratio as 1:2.…”
Section: Fabrication and Experimentsmentioning
confidence: 99%